2014
DOI: 10.3844/ajavsp.2014.182.188
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long Term Cadmium Chloride Exposure on Testicular Functions in Male Albino Rats

Abstract: This study was carried out to investigate the adverse effects of different doses of Cadmium Chloride (CdCl 2) on reproductive functions in male rats. Forty male albino rats weighted 100-130 g were equally divided into 4 groups. The control group received distilled water throughout the experimental period, while the three treated groups received 5, 50 and 100 ppm of CdCl 2 in drinking water for consecutive 100 days. At Day 100, all rats were sacrificed and immediately the reproductive organs were dissected and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…The results demonstrated that congestion and edema were present in the interstitial blood vessels, and sloughing of the spermatogenic cells resulted in central accumulation in the STs. These findings are consistent with those reported in other studies ( 31 , 35 , 36 ). The reported histopathological changes are mainly caused by disturbances in vascular permeability as a result of Cd toxicity ( 37 ).…”
Section: Discussionsupporting
confidence: 94%
“…The results demonstrated that congestion and edema were present in the interstitial blood vessels, and sloughing of the spermatogenic cells resulted in central accumulation in the STs. These findings are consistent with those reported in other studies ( 31 , 35 , 36 ). The reported histopathological changes are mainly caused by disturbances in vascular permeability as a result of Cd toxicity ( 37 ).…”
Section: Discussionsupporting
confidence: 94%
“…(2010) added that Cd exerted biological effects on the Sertoli cells, ensuing DNA damage and the presence of apoptotic cells. Fluid exudates were detected between some tubules, and these results were accorded with the findings of Elgawish and Ghanem (2014) and Li, Luo, et al (2016) who advocated that Cd chloride, results in oedematous and congestive changes in the interstitial blood vessels. They reported that the histopathological alterations are mainly triggered by disturbances in vascular permeability instigated by Cd toxicity (De Souza Predes, Diamante, & andDolder, H., 2010).…”
Section: Discussionsupporting
confidence: 86%
“…(c) A dose that affects testis and sperm and does not cause mortality in the test species. (d) Doses used by other investigators, orally administered to rodents: 5 mg/kg administered every 2 days (15 times) (El-Demerdash et al, 2004); 20 mg/kg/day for 6 weeks (Mohamed et al, 2014); 5 or 50 mg/L for 6, 12, and 24 weeks (Brzóska et al, 2003); 200 ppm for 5 weeks (Saïd et al, 2010); 200 mg/L for 5 weeks (Al-Ani et al, 2015); and 5, 50, and 100 ppm for 100 consecutive days (Elgawish and Ghanem, 2014). In this study, a linear relationship between concentration and exposure time was observed during the evaluation of Cd bioaccumulation in testis.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings agree with studies conducted by other investigators. Elgawish and Ghanem (2014), who used for their research doses of 5, 50, and 100 ppm of CdCl 2 in the drinking water, observed that with the last two doses, there was an increase in the percentage of abnormalities in the sperm of treated rats with respect to the controls. Al-Ani et al (2015) used a dose of 200 ppm of CdCl 2 orally administered.…”
Section: Discussionmentioning
confidence: 99%